Determinants of Capital Flight in Post War Sierra Leone: An Empirical Analysis - Tarawalie, Abu Bakarr; Jalloh, Talatu (International Journal of Economics and Financial Issues, 2021)
The objective of this paper is to investigate the determinants of capital flight in Sierra Leone and the direction of causality between capital flight and key variables, within the context of the autoregressive distributed lag (ARDL) estimation technique and the granger causality framework. The study utilizes quarterly data spanning the period 2000:Q1 to 2019:Q1. The bound test result confirms the existence of cointegration. The long run result reveals that real effective exchange rate, corruption and external debt are the main determinants of capital flight in Sierra Leone. Specifically, the finding indicates that real effective exchange rate, high level of corruption and accumulation of external debt cause an increase in capital flight. Furthermore, the result reveals that lagged capital flight, corruption, external debt and financial deepening are the main drivers of capital flight in the short run. Whilst lagged capital flight, corruption and external debt accumulation increase capital flight, the result reveals that a well-developed financial system reduce capital flight. The finding asserts that any disequilibrium in the model is corrected at the 26% adjustment speed annually. The diagnostic test confirms that the coefficients are stable, given that the CUSUM and CUSUMSQ lie within the critical band. The granger causality test results reveal that, external debt and capital flight exhibits bi-directional causality. However, both inflation and exchange rate demonstrate uni-directional causality, given that these variables granger cause capital flight, with no feedback effect. The study therefore urges the Government to take measures to strengthen the Anti-corruption Commission and the judiciary with a view to intensify the fight against corruption, and reduce capital flight. Also, government should put in place modalities to ensure strict capital controls, deepen the financial market and maintain broad macroeconomic stability as recipe to reduce capital flight. Keywords: ARDL, granger causality, capital flight, Sierra Leone, quarterly data JEL Classifications: C 32, F 21, F 40 DOI: https://doi.org/10.32479/ijefi.11271